The Impact of Cultural Contact, Destination Image, Smart Tourism technology and Memorable Experiences on Revisit Intention of Tourists through Tourist Satisfaction in Hebei Province of China - Shaoai, Han; Samarnbutra , Chanakiat; Sirichareechai, Worapoj (Journal of Roi Kaensarn Academi, 2024)
This study investigates the direct effects of cultural contact, destination image, smart tourism technology, and memorable experiences on tourists’ intention to revisit Hebei province. Adopting a quantitative research approach, data was collected through surveys from tourists visiting the province. Statistical techniques were employed for rigorous analysis of the collected data. The findings reveal significant associations between the studied factors and tourists’ satisfaction, which in turn positively influences their intention to revisit. Specifically, cultural contact and a positive destination image are identified as key factors enhancing tourists’ satisfaction. Furthermore, the effective use of smart tourism technology and the creation of memorable experiences are found to contribute significantly to satisfaction and revisit intention. These insights have important implications for tourism policymakers and industry stakeholders seeking to enhance tourist satisfaction and promote repeat visitation in Hebei province.